2010
DOI: 10.1007/s10495-009-0451-6
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Mediated regulation of the tumor suppressor protein, RASSF1A

Abstract: Death receptor-dependent apoptosis is an important mechanism of growth control. It has been demonstrated that Ras association domain family protein 1A (RASSF1A) is a tumor suppressor protein involved in death receptor-dependent apoptosis. However, it is unclear how RASSF1A-mediated cell death is initiated. We have now detailed 14-3-3 dependent regulation of RASSF1A-mediated cell death. We demonstrate that basal association of RASSF1A with 14-3-3 was lost following stimulation with tumor necrosis factor alpha (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…We have extensively described how RASSF1A can function as a pro-apoptotic modulator of death receptor signaling (Baksh et al, 2005;Foley et al, 2008;Ghazaleh et al, 2010). In the present study, we additionally describe how the presence of RASSF1A on microtubules may influence death receptor associations (Figures 2a and b) and endocytosis (Figure 3d), the stability of a-tubulin ( Figure 5) and tumor inhibition (Figure 7a).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We have extensively described how RASSF1A can function as a pro-apoptotic modulator of death receptor signaling (Baksh et al, 2005;Foley et al, 2008;Ghazaleh et al, 2010). In the present study, we additionally describe how the presence of RASSF1A on microtubules may influence death receptor associations (Figures 2a and b) and endocytosis (Figure 3d), the stability of a-tubulin ( Figure 5) and tumor inhibition (Figure 7a).…”
Section: Discussionmentioning
confidence: 66%
“…We next explored how RASSF1A polymorphisms may affect the ability to promote cell death. Two key elements seem to govern the initiation of RASSF1A-dependent cell death: the loss of self association (Foley et al, 2008) and the loss of association with 14-3-3 (Ghazaleh et al, 2010). If left unchecked (by either self associations or associations with 14-3-3), RASSF1A may promote uncontrolled cell death or be involved in abnormal growth-control mechanisms.…”
Section: Rassf1a Regulation Of Tubulin Stabilitymentioning
confidence: 99%
“…In the present study, the promoter methylation status of the APC and RASSF1A genes in cell-free DNA from patients with CRC was explored, and their incidence and potential correlations with different tumor parameters and survival were examined. RASSF1A protein is actively involved in microtubule regulation, genomic stability maintenance, cell-cycle regulation, apoptosis modulation, cell motility and invasion control (34)(35)(36). A number of studies have identified a high percentage of RASSF1A methylation in CRC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies demonstrated that RASSF8 interacts with the adapter protein 14-3-3 [107], an ubiquitously expressed scaffolding protein that regulates various molecular processes including apoptosis and cell cycle progression [108]. Interestingly, RASSF1A-mediated cell death can be regulated by 14-3-3 as well [109]. Thus, these adapter proteins appear to be pivotal in the functional regulation of RASSF proteins.…”
Section: Rassf8mentioning
confidence: 99%